RULE BASED DAN SAFETY STOCK UTUK MONITORING DATA WAREHOUSE PERUSAHAAN - Fitro Nur Hakim; Mokhamad Iklil Mustofa (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2018)
Abstrak A inventory system is created to maximize customer service and corporate profits, the system created by focusing on stockopname security. The method of rule base and safety stock, used to optimize inventory in warehouse / data warehouse. After the trial, the result rule / rule proven, so the stock in a secure position.